Stabilitas Serum Liofilisat Buatan Sendiri Sebagai Bahan Kontrol Kualitas Terhadap Parameter Blood Urea Nitrogen Dan Kreatinin - Diana Novita Sari (Analis Kesehatan Sains, 2023)
Improving health laboratory services is very much related to strengthening the quality of health laboratories. The control serum is part of the quality assurance of the health laboratory. Lyophilized serum is a type of homemade control serum. This research aims to determine the homemade lyophilized serum used as a control material for the parameters of Blood Urea Nitrogen (BUN) and creatinine which were analyzed for 2 months at a temperature of 2 - 8°C. This type of researvh is a quasi-experimental conducted at the Laboratory of Clinical Chemistry, Department of TLM Poltekkes, Ministry of Health, Surabaya and the pramita laboratory. Samples were obtained from the serum of students mahoring in TLM Poltekkes Kemenkes Surabay that has been qualified and were collected in one container for lyophilization. The average results of the BUN (Blood Urea Nitrogen) examination from week 1 to week 8 were 7.15 mg/dL, 7.15 mg/dL, 6.82 mg/dL, 7.12 mg/dL. dL, 7.12 mg/dL, 7.33 mg/dL, 7.15 mg/dL, 7.33 mg/dL, and 7.33 mg/dL. The average results of the creatinine examination from week 1 to week 8 were 0.69 mg/dL, 0.69 mg/dL, 0.70 mg/dL, 0.67 mg/dL, 0.72 mg/dL, 0.72 mg/dL, 0.68 mg/dL, 0.70 mg/dL. From the results of the examination, it can be concluded that the levels of BUN (Blood Urea Nitrogen) and creatinine in homemade serum lyophilized until the 8th week are still stable. Storage time for 8 weeks has no effect on BUN (Blood Urea Nitrogen) and creatinine levels in homemade lyophilized serum. Keywords : Home made lyophilized serum, BUN levels, Creatinine levels, material stability control